Advancing quality education through artificial intelligence / Dr. Hafizah Hammad Ahmad Khan, Noorlailahusna Mohd Yusof and Dr. Abdul Bari Khan - Ahmad Khan, Hafizah Hammad; Mohd Yusof, Noorlailahusna; Khan, Abdul Bari (Universiti Teknologi MARA, Kedah, 2024)
Sustainable Development Goal 4 (SDG 4) is a global initiative launched by the United Nations to achieve equitable and inclusive quality education for all by 2030. Conventional educational practices have typically followed a uniform curriculum and progress pace for all students. However, recent years have witnessed the emergence of artificial intelligence (AI) as a transformative force with the potential to improve education quality significantly. In particular, the pandemic caused by COVID-19 has further accelerated the growth of AI in education, as the closure of learning institutions necessitated alternative modes of learning (Rangel-Pérez et al., 2021). The impact of artificial intelligence (AI) on education has been a subject of interest in recent research. Several studies have highlighted the potential benefits of AI in enhancing education outcomes, including improving teacher effectiveness, fostering student engagement, and facilitating personalized learning (Dwivedi et al., 2021; Harry, 2023). According to Chen et al., (2020), AI has made administrative tasks such as grading assignments easier and improved teaching quality. Furthermore, it can personalize learning materials, enhancing students' learning experience. Similarly, Zheng et al. (2021) also found that AI has substantially and positively influenced students' learning achievements. AI has the potential to significantly enhance educational standards across multiple fields. Research has demonstrated that AI can enhance the learning environment and foster student motivation, creativity, and initiative (Huang et al., 2021). Moreover, AI technologies have been identified as promising tools for enhancing STEM education with the potential to boost teaching effectiveness and improve learning outcomes (Xu & Ouyang, 2022). Additionally, the integration of AI in education has the potential to advance the digitalization of education and present new opportunities for optimizing the education management process (Lin, 2022; Park & Kwon, 2023).